2019
DOI: 10.1002/adfm.201901880
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Action Flexible Antimicrobial Material: Switchable Self‐Cleaning, Antifouling, and Smart Drug Release

Abstract: A switchable material with a smart antimicrobial dual‐action functionality, which is based on a highly stretchable silicon polymer gradiently doped with polyyrrole, is proposed. The material exhibits superhydrophobic and self‐cleaning properties, high aerophilicity as well as the possibility of smart, electrically triggerable release of an incorporated drug. During the immersion of the material in water, an air gap is formed on its surface which prevents a formation of biofouling, attachment of microorganisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…[ 37 ] An effective strategy to solve the problem is to develop a switchable superwettable surface. For example, Deˇkanovský et al [ 38 ] reported a superhydrophobic and switchable material surface based on a highly stretchable silicon polymer doped with polypyrrole. In general, this surface underwater could form an air gap.…”
Section: Progress In Surface Modifications For Preventing Bacterial Adhesionmentioning
confidence: 99%
“…[ 37 ] An effective strategy to solve the problem is to develop a switchable superwettable surface. For example, Deˇkanovský et al [ 38 ] reported a superhydrophobic and switchable material surface based on a highly stretchable silicon polymer doped with polypyrrole. In general, this surface underwater could form an air gap.…”
Section: Progress In Surface Modifications For Preventing Bacterial Adhesionmentioning
confidence: 99%
“…These methods have a great disadvantage: they present some difficulties in the reproductibility of the process of surface modification, in particular in the case of the polymerization process of the MPC monomer. Alternative methods have been recently developed by use of active surfaces with electrically switchable hydrophobic/hydrophilic wettability targeted to prevent bacterial attachment and biofilm formation [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the precise control of the surface wetting is achieved, with related on-demand introduction of superhydrophobicity or water repellence. With such surface designs, smart activation of surface self-cleaning and bacterial repulsion functionality can be achieved [140][141][142]. In ref.…”
Section: Electro-responsive Coatingsmentioning
confidence: 99%